From Resilient to Thriving: Policy Recommendations to Support Health and Well-being in the Arctic - Cueva, Katie; Rink, Elizabeth; Lavoie, Josée G.; Healey Akearok, Gwen; Guistini, Sean; Kanayurak, Nicole; Stoor, Jon Petter A.; Larsen, Christina V.L. (The Arctic Institute of North America, 2022)
In 2018 – 19, eight Indigenous and non-Indigenous individuals from Canada, Greenland/Denmark, Sweden, and Alaska/United States came together to address research questions relevant to Arctic nations’ shared challenges and opportunities. Our work incorporated critical, community-based perspectives on Arctic health and well-being and promoted strengths-based approaches developed in partnership with Arctic communities. In this article we describe the group’s 16 action-oriented policy recommendations to support health and well-being in the Arctic in four thematic areas: 1) acknowledge and integrate Indigenous rights and knowledges, 2) implement meaningful action to address Indigenous determinants of health, 3) expand health-oriented monitoring and assessment programs, and 4) implement community-led, critical research approaches that focus on partnerships, reciprocity, adherence to ethical guidelines, and funding community-based research. Our recommendations are actionable guidelines for policy and research aimed at reducing inequities, supporting Indigenous expertise and existing knowledge, and promoting thriving communities in the Arctic. En 2018-2019, huit personnes autochtones et non autochtones du Canada, du Groenland (Danemark), de la Suède et de l’Alaska (États-Unis) se sont réunies pour discuter de questions de recherche se rapportant aux défis et aux occasions se présentant dans les nations de l’Arctique. Notre travail a tenu compte de perspectives critiques et communautaires sur la santé et le bien-être dans l’Arctique, en plus de promouvoir des approches fondées sur les points forts, approches élaborées de concert avec des collectivités de l’Arctique. Dans cet article, nous décrivons les 16 recommandations de politiques axées sur des actions formulées par le groupe. Ces recommandations ont pour but de favoriser la santé et le bien-être dans l’Arctique et portent sur quatre grands thèmes : 1) reconnaître et intégrer les droits et les connaissances des Autochtones; 2) mettre en oeuvre des actions ...